Draft Genome Sequences of Four Strains of Vibrio parahaemolyticus, Three of Which Cause Early Mortality Syndrome/Acute Hepatopancreatic Necrosis Disease in Shrimp in China and Thailand - Yang, Yi-Ting (American Society for Microbiology, 2014)
We sequenced four Vibrio parahaemolyticus strains, three of which caused serious acute hepatopancreatic necrosis disease. Sequence analysis of the virulent strains revealed not only genes related to cholera toxin and the type IV pilus/type IV secretion system but also a unique, previously unreported, large extrachromosomal plasmid that encodes a homolog to the insecticidal Photorhabdus insect-related binary toxin PirAB.